Potensi Khamir Amilolitik Sebagai Starter Fermentasi Produk Pangan Peternakan - Cahyaningsih, Ananda Winda; Pratama, Andry; Gumilar, Jajang (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Fermentation is a food processing technique that has been used for a long time and offers increased shelf life and sensory quality of the product. One of the microorganisms that has great potential as a fermentation starter is amylolytic yeast which has the ability to break down starch into simple sugars through the enzyme amylase. This research aims to review the potential of amylolytic yeast in the fermentation of livestock food products, covering various types, characteristics and applications in the livestock product food industry. This research uses a literature review method from various scientific sources in the last 10 years. The analysis results revealed the characteristics of amylolytic yeast, including tolerance to environmental variations and adaptability to various food substrates. Various types of yeast such as Saccharomyces cerevisiae, Candida, Debaryomycces have been proven effective in improving sensory quality, nutritional value, and production efficiency in livestock food products.